WhatsApp: diálogos e atos de escrita na era digital - Silva, Adriana Naomi Fukushima da [UNESP]; Santos, Sônia de Oliveira [UNESP]; Arena, Dagoberto Buim [UNESP]; Soares, Thariane Nayara Leite [UNESP]; Rosa, Lilian Camila [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
This work is a fragment of a larger study entitled Writing and reading on screens supported and financed by PROGRAD-Core Teaching / UNESP Marilia. The general objective is to offer students the opportunity to develop the field of reading and writing on screens, in general, and through the application of use in nomadic digital devices such as tablets and mobile phones. The research takes place in the morning, once a week, starting at 9 am, in a welfare ONGs and education located in the suburb of west of the city of Marilia / SP. With the participation of the coordinator teacher, two graduation students of the pedagogy course, one graduate student, one doctoral student, and fifteen children aged between 6-9 years. There are two lines of actuation: the development and acquisition of written language in discursive process, with the keystroke as a new form registration tool on media like the screen, using the WhatsApp application, and the act of learning to read as a cultural act evolving in film sessions with subtitled films. Therefore, this paper discusses the data generated during the writing instant messaging via WhatsApp. Based on the data generated to date it is concluded that by using the WhatsApp application in messaging, children soak in the world of written culture full of meaning and choices of statements and all graphic signs happen in real situation of exchange discursive.

Este trabalho é um recorte de uma pesquisa maior intitulada Escrever e ler em telas apoiada e financiada pela PROGRAD-Núcleo de Ensino/UNESP- Marília. O objetivo geral é o de oferecer a crianças a possibilidade de desenvolver o domínio da leitura e da escrita em telas, de modo geral, e por meio do uso de aplicativos em aparelhos digitais nômades, principalmente celulares. A pesquisa ocorre no período da manhã, uma vez na semana, com início às 9 horas, em uma ONG de assistência social e educação localizada em bairro periférico da zona oeste da cidade de Marília/SP. Conta com a participação do professor coordenador, duas graduandas do curso de pedagogia, uma mestranda, uma doutoranda, e quinze crianças com faixa etária entre 6 a 9 anos. Existem duas linhas de atuação: o desenvolvimento e a aquisição da língua escrita em processo discursivo, com o uso do teclado como ferramenta de nova forma inscrição em suportes como a tela, com o uso do aplicativo WhatsApp, e a aprendizagem do ato de ler como um ato cultural em sessões cinematográficas com filmes legendados. Diante disso, esse trabalho discute os dados gerados durante a escrita de mensagens instantâneas via WhatsApp. Com base nos dados gerados até o momento conclui-se que ao utilizar o aplicativo WhatsApp na troca de mensagens, as crianças mergulham no mundo da cultura escrita repleta de sentido e as escolhas dos enunciados e de todos os sinais gráficos ocorrem em situação real de interação verbal discursiva.
Keywords: Education; WhatsApp; Acts of writing; Educação; WhatsApp; Atos de escrita